Etos Kerja Pedagang Etnis Madura di Pusat Grosir Surabaya Ditinjau Dari Etika Bisnis Islam - Faraby, Muhammad Ersya; Faiza, Siti Inayatul (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Natural resources have not been well managed in Madura and the low level of human resources leads to ethnic Madurese communities abroad to obtain a decent life by applying a high work ethic. This research aims to know the work ethic of ethnic Madurese in Central merchant Wholesale Surabaya reviewed from Islamic business ethics.Approach used in this research is qualitative approach to method case study is descriptive. Data done with interview observation and documentation against traders ethnic madura in central wholesale Surabaya. For data advocates derived from data given by centers management wholesale Surabaya. Besides is also study library and literature about ethos work ethnic Madurese and Islamic business ethics.The results obtained are the informants argued most of the Madurese ethnic merchants in wholesale center Surabaya interpret and apply the Madurese ethnic work ethic that is hard work and wander, as well as in implementing the work ethic they comply with Islamic business ethics.